O problema da matéria escura: astrofísica contemporânea no ensino de física - Souza, Diego Corrêa Peres de (My University, 2024)
This work presents a research study that investigates how a didactic sequence focused on the presentation and discussion of dark matter in teaching-learning processes in high school physics classes can influence the understanding of some basic physics concepts. To theoretically support this dissertation, the ideas of Gaston Bachelard were used, especially the concepts of epistemological profile and epistemological obstacles. The didactic sequence was applied in a third-year high school class at a public school in Flores da Cunha, Rio Grande do Sul. The analysis of the results led to the development of an improved version of the didactic sequence, resulting in the educational product of this dissertation. The results indicate a significant positive potential for the implementation of the theme of dark matter in discussions at the high school level. [resumo fornecido pelo autor]
Este trabalho apresenta uma pesquisa que investiga como uma sequência didática focada na apresentação e discussão sobre matéria escura nos processos de ensino-aprendizagem em aulas de física do Ensino Médio pode influenciar no entendimento de alguns conceitos de física básica. Para fundamentar teoricamente esta dissertação, foram utilizadas as ideias de Gaston Bachelard, especialmente os conceitos de perfil epistemológico e obstáculos epistemológicos. A sequência didática foi aplicada em uma turma do 3º ano do Ensino Médio de uma escola pública em Flores da Cunha, Rio Grande do Sul. A análise dos resultados permitiu a elaboração de uma versão aprimorada da sequência didática resultando no produto educacional desta dissertação. Os resultados indicam um potencial positivo significativo para a implementação da temática da matéria escura em discussões no nível de Ensino Médio. [resumo fornecido pelo autor]
Keywords: Física - Estudo e ensino; Física (Ensino médio); Aprendizagem; Physics - Study and teaching; Physics ( High school); Learning